Zeitschrift für die neutestamentliche Wissenschaft (De Gruyter, 1900)
A highly reputed journal published since 1900, the Zeitschrift für die neutestamentliche Wissenschaft is an international journal for the exegesis of the New Testament and knowledge of the early church (patristics).